2005
DOI: 10.1115/1.2193547
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effect of Laser Beam Geometry on Laser Transformation Hardening

Abstract: The effect of transformation hardening depends upon both heating and cooling rates. It is desirable to have a slow heating rate and a rapid cooling rate to achieve full transformation. To date laser transformation hardening has been carried out using circular or rectangular beams which result in rapid heating and cooling. Although the use of different beam intensity distributions within the circular or rectangular laser beams has been studied to improve the process, no other beam geometries have been investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…They adapted two criteria to predict the quantity of the laser cutting operation. The effect of laser beam geometry on laser transformation hardening was investigated by Safdar et al [6]. They showed that none of the circular and rectangular beams had optimum shapes for transformation hardening; however, triangular beam geometry was shown to produce the best thermal history for achieving transformation hardening.…”
Section: Introducionmentioning
confidence: 98%
“…They adapted two criteria to predict the quantity of the laser cutting operation. The effect of laser beam geometry on laser transformation hardening was investigated by Safdar et al [6]. They showed that none of the circular and rectangular beams had optimum shapes for transformation hardening; however, triangular beam geometry was shown to produce the best thermal history for achieving transformation hardening.…”
Section: Introducionmentioning
confidence: 98%
“…Safdar et al [16] have reported that both the heating and cooling rates influence the outcome of hardening achieved during LSH and that higher hardness was observed with lower heating rates. Obviously, the result here is different; the possible reason is the heating rate and peak temperature both being high enough in the case of shaped beam 2, as shown in Fig.…”
Section: Microhardnessmentioning
confidence: 99%
“…Equation [13] is the solution of the temperature distribution in an infinite solid due to the quantity of heat Q instantaneously generated at t ¼ 0 at a point (x 0 , y 0 , z 0 ). However, if this solution is introduced for an instantaneous source of heat in a substance lying in the plane z ¼ 0 and in the absence of radiation heat loss from the surface, the solution yields:…”
Section: Mathematical Modeling Of Laser Nonconduction Heating Of Two-mentioning
confidence: 99%
“…Considerable research studies were carried out to examine laser melting of metallic surfaces (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). As the heating duration or the intensity of the laser beam increases, phase change takes place at the irradiated surface.…”
Section: Introductionmentioning
confidence: 99%